Probing the nature of the χc1(3872) state using radiative decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Herrero Gascón, Paula; Marks, Jörg; et al. (Journal of high energy physics, 2024)
The radiative decays chi(c1)(3872) -> (2S) gamma and chi(c1)(3872) -> J/gamma are used to probe the nature of the chi(c1)(3872) state using proton-proton collision data collected with the LHCb detector, corresponding to an integrated luminosity of 9 fb(-1). Using the B+ -> chi(c1)(3872)K+ decay, the chi(c1)(3872) -> psi(2S) gamma process is observed for the first time and the ratio of its partial width to that of the chi(c1)(3872) -> J/psi gamma decay is measured to be Gamma(chi c1(3872))->psi(2S)gamma/Gamma(chi c1(3872)) -> J/psi gamma = 1.67 +/- 0.21 +/- 0.12 +/- 0.04, where the first uncertainty is statistical, the second systematic and the third is due to the uncertainties on the branching fractions of the psi(2S) and J/psi mesons. The measured ratio makes the interpretation of the chi(c1)(3872) state as a pure D-0(D) over bar (*0) + (D) over bar D-0(*0) molecule questionable and strongly indicates a sizeable compact charmonium or tetraquark component within the chi(c1)(3872) state.
Im Text ist "X", "c" und "1" tiefgestellt
Gesehen am 10.11.2025